Hate crime, policing, and the deployment of racial and cultural diversity - Bryan, Timothy (Oñati Socio-Legal Series, 2020)
This paper examines how diversity is mobilized and deployed as a form of hate crime response in the York Regional Police Service, and how commitments to racial and cultural diversity embedded in the framework of hate crime policy are interpreted by police officers engaged in the frontline policing of hate crimes. Hate crime policies and specialized training programs in Ontario were developed around two central foci: 1) traditional policing concerns involving proper investigative techniques, evidence collection, documentation, and officer roles and responsibilities; and 2) emerging concerns regarding victim care, community relations, and commitments to racial and cultural diversity. Drawing on interviews with officers stationed at all five of the Service’s divisional locations, this paper shows how commitments to diversity embedded in the Service’s approach to hate crime exist along-side, and in conflict with, officer perceptions that see diversity as a source of the problem of hate.